Use of artificial substrate in pond culture of freshwater prawn (Macrobrachium rosenbergii): a new approach regarding growth performance and economic return - Dilshad Milky Tuly; Md. Sherazul Islam; Mst. Hasnahena; Md. Rezwanul Hasan; Md. Tawhid Hasan (Journal of Fisheries, 2014)
An experiment was conducted for six months to evaluate the effects of artificial substrates on the survival, growth and production of Macrobrachium rosenbergii juveniles. The treatment T1 contained locally available bamboo-made substrate both vertical and horizontal and treatment T2 received no substrate. Juvenile prawns (0.40±0.13 g) were stocked at the rate of 19,760 prawns ha-1. The water quality parameters range such as temperature, pH and DO were 22.06-33.45°C, 7.70-8.40 and 4.75-6.15 mgl-1 respectively which was no significant difference (P<0.05) between two treatments. The final weight was 56.48±6.56 g and 45.03±2.11 g in T1 and T2 respectively. The survival rate of T1 was 63.12% which was significantly higher (P>0.05) than T2 (56.87%). The specific growth rate, food conversion ratio and protein efficiency ratio were 1.19 % and 1.14 %, 3.15 and 4.39, 0.98 and 0.71 in T1 and T2 respectively which were not significantly different (P<0.05) between treatments. The total production and net profit in T1 was 1408 kgha-1 and BDT 117,325 ha-1 which was significantly higher (P>0.05) than T2. Thus growth and survival of prawn juveniles improved in presence of artificial substrate which could be economically viable technique for the freshwater prawn culture.